2011
DOI: 10.1186/1471-2458-11-835
|View full text |Cite
|
Sign up to set email alerts
|

Who wants a slimmer body? The relationship between body weight status, education level and body shape dissatisfaction among young adults in Hong Kong

Abstract: BackgroundBody shape dissatisfaction has been thought to have an indispensable impact on weight control behaviors. We investigated the prevalence of body shape dissatisfaction (BSD) and explored its association with weight status, education level and other determinants among young adults in Hong Kong.MethodsInformation on anthropometry, BSD, and socio-demographics was collected from a random sample of 1205 young adults (611 men and 594 women) aged 18-27 in a community-based household survey. BSD was defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 37 publications
4
37
1
5
Order By: Relevance
“…Whilst the focus is on obesity, the literature investigates factors associated with BMI [see [49][50][51][52] and the variables commonly identified are also associated with health status. It may be that poor body image leads somebody to report poor health [53].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the focus is on obesity, the literature investigates factors associated with BMI [see [49][50][51][52] and the variables commonly identified are also associated with health status. It may be that poor body image leads somebody to report poor health [53].…”
Section: Discussionmentioning
confidence: 99%
“…A structured questionnaire with a with figure-rating scale for girls (silhouettes) validated and widely used in other studies [18,19], a head teacher key informant interview (KII) guide and a focus group discussion (FGD) guide were used to collect data. All data collection instruments were pretested in a fifth school that was not part of the main study.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to our findings, previous studies have found that approximately 40 % of pre-adolescent girls (2,17,26,27) and about 30-35 % of boys want to be thinner (1,2) . A study of adolescent girls in HK (5) , and another of 18-27-year-old HK Chinese adults (28) , found that 75 % expressed a desire to be thinner, a considerably higher prevalence than that Ref.…”
Section: Main Findingsmentioning
confidence: 98%